Protecting crops and feeding livestock - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
Ansumana Jarjue, Principal Research Officer for agroforestry at NARI in The Gambia explains how agroforestry trees can help livestock farmers.